Review—The Beautiful Molecule: 30 Years of C60 and Its Derivatives. (1st January 2017) - Acquah, Steve F. A.; Penkova, Anastasia V.; Markelov, Denis A.; Semisalova, Anna S.; Leonhardt, Branden E.; Magi, James M.
Abstract : In 1996 Sir Harold W. Kroto, Robert F. Curl and Richard E. Smalley were honored with the Nobel Prize in Chemistry for the discovery of fullerenes. The advent of these new forms of carbon heralded a race to understand the physical and chemical properties. C60 is virtually insoluble in polar solvents but is partially soluble in benzene, toluene, and carbon disulfide. This made the processing of fullerenes for new applications fairly problematic. However, the physical and chemical properties of these cage structures may be tailored for a wide range of applications. Some of the difficulties in processing have been overcome by using novel fullerene derivatives. The functionalization of the fullerene core with different chemical moieties provided a vector toward potential applications in drug delivery, optoelectronics, electrochemistry and organic photovoltaics. In this review, we will take a closer look at the features of some of the fullerene derivatives that have reinvigorated the field of fullerene research. Water-soluble polyhydroxylated fullerenes such as fullerenol have demonstrated the potential for good electron transfer and optical transmission, while hydrophobic fullerene derivatives have shown promising avenues for catalytic applications. 2015 marked the 30 th anniversary of the discovery of fullerenes, with celebrations around the world including an event by the Royal Society of Chemistry, bringing together many of Sir Harold Kroto's former students. The event also coincided with the recent discovery of C60 + in space after a complex twenty-year search. It is with sadness that we, Harry's Research Group at Florida State University, and his international collaborators, reflect on the passing of Sir Harold Kroto. His dedication to science and commitment to science communication through the VEGA Science Trust and the Global Educational Outreach for Science Engineering and Technology (GEOSET) initiative help to raise awareness of the challenges for science in the modern world. We will continue to inspire young students through outreach activities he initiated.